Government–Business Relationships and Corporate Poverty Alleviation Decisions: Evidence from the People’s Republic of China - ZHEN WANG; KAI WU (Asian Development Review)
This study investigates the impact of government–business relationships on corporate involvement in the People’s Republic of China’s poverty alleviation campaign. Using data on Chinese-listed firms from 2017 to 2020, we find that closer government–business relationships, as measured by a comprehensive index, are associated with less corporate poverty alleviation participation and investments in targeted poverty alleviation initiatives. We establish causality through instrumental variables and address the endogeneity concerns. Our analysis reveals that this negative association is attenuated in firms with higher Communist Party involvement and in cities with better fiscal conditions and increased marketization levels. We also elucidate risk-taking and agency cost channels through which the government–business relationships suppress corporate poverty alleviation. Our findings suggest that reconstructing government–business relationships breeds substitution between the public and private provisions of social services. This study contributes to the literature on political connections, corporate social responsibility, and public–private dynamics in addressing societal challenges.